Acute 'pathological haematoma' without significant antecedent trauma as an unusual presentation of undiagnosed malignancy. (28th June 2012) - Clement, Rhys Gareth Ellis; Cozens, Neil; Sharp, Jerry; Minhas, Honeyia
Abstract : The authors report two cases of malignancy that presented initially with acute haematomas without any history of significant trauma. The first case was a 31-year-old male who presented with a large haematoma in the anterior triangle of the neck following minor trauma during a rugby match. This was shown to be due to haemorrhage into an undiagnosed papillary thyroid tumour. The second case was a 41-year-old male who developed a spontaneous sternocleidomastoid haematoma after laying flagstones and without any history of direct trauma. This was due to haemorrhage into a nodal deposit of non-Hodgkin's lymphoma. These cases highlight that sudden onset haematomas without obvious explanation may be the result of underlying malignancy. In such instances further investigation must be considered and re examination of the patient is essential after the haematoma has resolved.